Energy Metabolism of Sheep Supplemented with Complete Rumen Modifier (CRM) - Miftahuddin Ahmad; Fransisca Maria Suhartati; Muhamad Bata (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
This study aimed to examine the effect of supplementing the Complete Rumen Modifier (CRM) which consisted of 30% Morinda citrifolia leaf flour, 30% Camellia sinensis leaf dregs flour, 30% Ipomoea batatas leaf flour, 3% S. cerevisiae, 3% metionin and 3% sulfur on the energy metabolism of 18 local male sheep aged 6-8 months. The experimental feed consisted of ammoniated rice straw and concentrate (40:60) weighing 4% DM body weight. This study was subjected to a randomized complete block design (RCBD), analyzed six groups of initial weight of sheep allotted into three treatment groups: 0%, 1%, and 2% CRM of DM feed. The measured variables were energy intake (EI), digestible energy (DE), metabolizable energy (ME), energy retention (RE), and efficiency of RE to EI, RE to DE, and RE to ME. The results showed significant effects (P<0.01) of supplementing CRM in the feed on EI, DE, ME, RE, and efficiency of RE to EI, RE to DE, and RE to ME. The orthogonal polynomial test revealed that a higher dose of CRM supplementation in the feed has quadraterally increased (P<0.01) EI, DE, ME, and RE with peak points on 0,62%; 0,80%; 1,05%; 1,09%, respectively, and linearly increased (P<0.01) the efficiency of RE to EI, RE to DE, and RE to ME. It was concluded that the addition of CRM at the level of 2% was able to produce optimal energy efficiency in sheep.